Empirical examination of the ability of children to consent to clinical research. Issue 3 (June 1998) - Ondrusek, N; Abramovitch, R; Pencharz, P; Koren, G
Abstract : This study examined the quality of children's assent to a clinical trial. In subjects younger than 9 years of age, understanding of most aspects of the study was found to be poor to non-existent. Understanding of procedures was poor in almost all subjects. In addition, voluntariness may have been compromised in many subjects by their belief that failure to complete the study would displease others. If the fact that a child's assent has been obtained is used to justify the exposure of that child to the potential harm of a non-therapeutic blood sample, the assent must be meaningful. In the nutrition study observed here, the quality of the assent of children younger than 9 years of age was very poor. The assent therefore did not provide a valid justification for requesting a blood sample from these children. This study indicates that most children younger than 9 years of age cannot be expected to consent or assent to clinical research in a meaningful way. The current age of 7 years for initiating assent (in addition to parental consent) is possibly not appropriate and should be reconsidered.